PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BLOOKET TERHADAP KEMAMPUAN MENULIS TEKS ANEKDOT SISWA KELAS X SMA SWASTA KRISTREN IMMANUEL MEDAN - lyana Moi Lingga; Sarma Panggabean; Pontas Jamaluddin Sitorus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effect of the Blooket learning media on the anecdotal text writing skills of tenth-grade students at Immanuel Christian Private Senior High School Medan. This study employed a quantitative research method. The population consisted of all 28 tenth-grade students at Immanuel Christian Private Senior High School Medan. The sampling technique used was saturated sampling (total sampling) because the population was relatively small and consisted of only one class. Saturated sampling is a technique in which all members of the population are included as research participants. After the implementation of different treatments, the mean pretest score was 55.25 with a standard deviation of 10.51, while the mean posttest score was 77.93 with a standard deviation of 9.00. The prerequisite test results indicated that the data were normally distributed and homogeneous. Subsequently, a one-tailed t-test was conducted at the significance level of α = 0.05. The results of the t-test showed that the use of Blooket learning media had a significant effect on the anecdotal text writing skills of tenth-grade students at Immanuel Christian Private Senior High School Medan. The final achievement was categorized as good.